Implementation Outcomes and Their Determinants for Hospital‐Led Care Coordination Interventions Targeting Patients With Complex Care Needs: A Qualitative Systematic Review. - Malakellis, Mary; Wong Shee, Anna; Wood, Sarah; Alston, Laura; Beks, Hannah; Murray, Margaret; Versace, Vincent L.; Mc Namara, Kevin (Journal of Clinical Nursing (John Wiley & Sons, Inc.), 2026)
Aim: To describe the implementation determinants for care coordination interventions in a hospital context. Design: Systematic review. Methods: This review was guided by the Consolidated Framework of Implementation Research (CFIR), assessed for quality using the Mixed Methods Appraisal Tool and reported with the PRISMA guidelines. Data Sources: CINHAL Complete, EMBASE, MEDLINE Complete, PsychINFO (between January 1, 2013, and December 31, 2022, and updated May 09, 2024) and a manual reference list search of all included studies. Results: The search returned 5614 articles after duplicates were removed. After title and abstract screening, 264 articles underwent full‐text review. Sixteen studies (15 care coordination models) met the inclusion criteria. The CFIR inner setting domain and the implementation process domain were the most prominent domains and 'Partnerships & Connections', 'Work Infrastructure', 'Capability' and 'Reflecting and Evaluating' subdomains emerged as important determinants across the included studies. Conclusion: Inconsistent findings relating to care coordination outcomes are likely to be substantially influenced by the complexity and heterogeneity of the interventions and variations in implementation and contextual factors. Intra‐ and inter‐organisational relationships were important to connect previously disconnected parts of the health system and were facilitated by experienced care coordinators. Continual improvement was also important to increase fit with contextual factors. More high‐quality studies are needed to identify commonalities and provide generalisable principles and characteristics associated with high‐performance implementation. Implications for the Profession and/or Patient Care: Review findings will provide practitioners, policymakers, and researchers with a comprehensive synthesis of evidence underpinning implementation of effective community care coordination from hospital settings. Impact: These review findings will inform the effective implementation of care coordination interventions in a hospital context for patients with complex multimorbidity. Reporting Methods: Preferred Reporting Items for Systematic reviews and Meta‐Analysis. Trial and Registration: PROSPERO Registration: CRD42022376642. Patient or Public Contribution: No patient or public Contribution.